The Effect of The Deep Learning Approach in Learning the Game of Rounders on the Cooperative Character of Elementary School Students - Dinda Astiana Salsabila; Ayi Suherman; Tedi Supriyadi (Journal of Physical Education Health and Sport, 2026)
Physical education in primary schools not only enhances motor skills and physical health but also significantly contributes to the development of student teamwork. Although team sports such as rounders can promote collaboration, traditional pedagogical methods sometimes emphasise performance at the expense of substantive social engagement, highlighting the necessity for more effective educational strategies. This study aimed to examine the effect of an immersive learning approach in the game of rounders on elementary school students’ understanding of cooperation and to compare its effectiveness with that of conventional teaching methods. This study used a quantitative, quasi-experimental design with a non-equivalent control group. Participants were sixth-grade students divided into two groups: an experimental group that received immersive instruction and a control group that received traditional instruction. Data were collected using a cooperation questionnaire administered before and after the intervention. The instrument used a Likert scale and was tested for validity and reliability before use. Data analysis included descriptive statistics and inferential analysis to examine intra-group improvements and inter-group differences. Results showed that both groups improved their understanding of cooperation after the learning process; however, the experimental group showed significantly more improvement than the control group. Statistical testing confirmed a significant difference between the two groups after the intervention, indicating that the immersive learning approach was more effective in improving students’ understanding of cooperation. The learning process, which incorporated reflection, discussion, and collaborative problem-solving, led to deeper, more meaningful student engagement. In conclusion, integrating an immersive learning approach into rounders instruction positively influenced students’ understanding of cooperation. This can be considered an effective strategy to improve the quality of physical education teaching in elementary schools.